Synthesis and diffraction, computational exposure, hardness and interaction studies of EN2MNYM3NA crystalline material for mechanized, electronic and bio utilities. (2022) - Ramabalan, S.; SenthilKannan, K.; Suganya, K.; Flora, G.; Manikandan, R.; Vimalan, M.
Abstract: (E)-N-[(2-methoxynaphthalen-1-yl) methylidene]-3-nitroaniline - EN2MNYM3NA crystal is grown by slow evaporation solution growth method. The studies such as single crystal XRD, PXRD, unit cell, 3Dimensional pattern, Fourier impact and Laplace level interactive as well as Hirshfeld interactions data with the finger print profile, the weak force blow and profile are completed. The lattice constants with a, b, c values as 12.8482 Å, 15.4087 Å, 7.6234 Å and beta as 98.04 O and volume as 1509.23 Å 3 with material's chemical formula as C18 H14 N2 O3 The weak interactions of 50% and 75% are well enunciated with value of n as 2.93 for hardness coefficient; the anti-diabetic value for macro scaled EN2MNYM3NA as 39.92 (IC50 ) and the resolution and the elevated Isovalue value is 0.5; Globularity value as 0.721; Asphericity as 0.198; The scalings for the versatile energy and electron densities are well measured and reported properly.